Menyambut Ulang Tahun Kemerdekaan Republik Indonesia Ke 78 Di Lingkungan Kampung Mawokau Jaya - Longginus Gelatan; Ahmad Tomu; Murnitasari Murnitasari (STIE Jambatan Bulan, 2024)
The purpose of this service is to beautify the Maukow Jaya village environment so that it is ready to welcome the 78th birthday of the Republic of Indonesia. This activity can also add enthusiasm in celebrating the birthday of the Republic of Indonesia. All activities are the result of cooperation between the team and village officials and the community in the Maukow Jaya village environment. This service activity received a good response from the village head and the community in the Mawokau Jaya Village Environment. This can be seen from the gratitude from the village head because this activity can not only beautify the Mawokau Jaya Village Environment but can also arouse the spirit of nationality and love for the country.